Pendampingan Optimalisasi Manajemen Asuhan Gizi Pasien melalui Penerapan Electronic Mecial Record (EMR) dengan QR Code dan Whatsapp Bot di NCC - Rossalina Adi Wijayanti; Riskha Dora Candra Dewi; Novita Nuraini (P3M Politeknik Negeri Jember, 2025)
The Nutrition Care Center (NCC) at Politeknik Negeri Jember (Polije) functions as a Teaching Factory (TEFA), providing comprehensive nutritional assessment, diagnostic services, nutritional counseling, and tailored dietary plans for clients. Health services, including nutrition, necessitate accurate medical records encompassing patient identification, examinations, treatments, interventions, and other pertinent information. However, NCC's manual paper-based medical records system faces challenges. It uses age-based instead of date of birth-based record numbering, lacks standardized nutrition assessment, and lacks disease code classification. This manual system is prone to damage, loss, and demands considerable time and storage space. Since its establishment in November 2021, NCC has seen a steady increase in both internal and external clients. Collaborations with educational institutions, offices, and senior citizen groups have further boosted visits. To enhance efficiency, NCC plans to implement Electronic Medical Records (EMR) with QR Codes and WhatsApp Bots. This approach aims to simplify access to clients' medical histories, allergies, and previous therapies, while also streamlining record retrieval. EMR integration is vital in managing the complexity of nutritional services and supports NCC's mission to provide high-quality care. This initiative aligns with the 2022 Health Department's Research Masterplan and the development of TEFA services. It also reflects the growing trend of using technology, including mobile apps and Artificial Intelligence, in healthcare services. In summary, the increasing number of clients and collaborative screenings with external institutions have led to complex medical records. NCC recognizes the need for a more efficient system and proposes implementation of EMR with QR Codes and WhatsApp Bots to optimize patient care. The project's outcomes will include publications, videos, and improved partner capabilities in EMR usage for patient nutrition care at NCC.